In Situ Reconfigurable Continuum Robot with Varying Curvature Enabled by Programmable Tensegrity Building Blocks - Jie Zhang; Junhao Shi; Junhai Huang; Qihuan Wu; Yuwen Zhao; Jinzhao Yang; Hamed Rajabi; Zhigang Wu; Haijun Peng; Jianing Wu (Advanced Intelligent Systems, 2023)
Reconfigurable continuum robots exhibit programmable interaction capability, enabling them to cope with challenges poorly addressed by conventional rigid robots. However, the regulation of the module type and/or sequence may result in time‐consuming and labor‐intensive problems. Therefore, in situ reconfiguration schemes are required to develop in a simple yet robust solution for continuum robot design. Herein, inspired by the structure characteristics of the seahorse tail, an original template based on a tensegrity building block (TBB) for creating an in situ reconfigurable continuum robotic paradigm is proposed. As the length of the stretchable struts in the TBB could be programmed, five typical homologous types from the template are derived. Then, ten TBBs into a continuum robot are assembled and the multi‐body dynamic framework is employed to develop a mechanical model for predicting the profile after deformation. Theoretical predictions demonstrate that the robotic shape can be customized in situ by switching the type of TBBs, without disassembling the robot. Furthermore, the tailored continuum robotic configurations are applied to conformally interact with the varying‐curvature objects. The experimental results suggest that the proposed programmable template offers a facile and rapid reconfiguration scheme for the continuum robots, which greatly improves the robotic interaction capability.